Densities Non-Realizable as the Jacobian of a 2-Dimensional Bi-Lipschitz Map Are Generic - Viera-Quezada, R (World Scientific Publishing Co. Pte Ltd, 2018)
In this work, positive functions defined on the plane are considered from a generic viewpoint, both in the continuous and bounded setting. By pursuing on constructions of Burago-Kleiner and McMullen, we show that, generically, such a function cannot be written as the Jacobian of a bi-Lipschitz homeomorphism. © 2018 World Scientific Publishing Company.